Determinants affecting choices of dining at hotel restaurants in Kuala Terengganu / Fatimah Abd Ghani … [et al.] - Abd Ghani, Fatimah; Mohamad Zuki, Muhamad Syukri; Khaidir, Adieb Khuzairie; Ramli, Noorazlin; Hamid, Munirah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Every hotel customer must undergo a selection phase before deciding the hotel restaurant they want to dine in. This study was conducted to identify the factors influencing customers' dining decisions at hotel restaurants. Only four hotels, specifically in Kuala Terengganu, were used to collect data from the hotel guests: Paya Bunga Hotel, Raia Hotel, Primula Hotel, and Duyung Marina. Questionnaires were distributed to the sample subjects to collect data. The data was then analysed to determine whether the variables were related to determinants affecting choices of dining at restaurants in hotels. Therefore, the findings can only be gathered from the populations of domestic travellers and residents. The outcomes of this research discovered that price and promotion significantly influence a person’s dining choice at hotel restaurants. Additionally, it implies that the overall population constrained the results.